2012
DOI: 10.1371/journal.pone.0029084
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine Improved Laboratory-Measured Decision-Making Performance in Abstinent Heroin Addicts

Abstract: BackgroundImpulsivity refers to a wide spectrum of actions characterized by quick and nonplanned reactions to external and internal stimuli, without taking into account the possible negative consequences for the individual or others, and decision-making is one of the biologically dissociated impulsive behaviors. Changes in impulsivity may be associated with norepinephrine. Various populations of drug addicts all performed impulsive decision making, which is a key risk factor in drug dependence and relapse. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 50 publications
0
9
1
Order By: Relevance
“…Previously, several attempts have been made to enhance decision-making using pharmacological interventions. However, up to now results are inconsistent (2729). The possibility of using psychosocial interventions may open a new window in developing new, more specific interventions.…”
Section: Discussionmentioning
confidence: 90%
“…Previously, several attempts have been made to enhance decision-making using pharmacological interventions. However, up to now results are inconsistent (2729). The possibility of using psychosocial interventions may open a new window in developing new, more specific interventions.…”
Section: Discussionmentioning
confidence: 90%
“…In studies that reported on groups that had been abstinent for an average of less than one month, these groups were classified as current users (Cheng et al, 2012;Kirby and Petry, 2004). For studies that reported baseline and follow-up testing using a behavioural measure, only the baseline values were entered into analyses (Baldacchino et al, 2015;Zhang et al, 2012). For studies that reported data for two or more decision-making measures (Ahn and Vassileva, 2016;Upton et al, 2012), effect sizes for each separate decision-making measure were pooled to create a combined decision-making effect size estimate.…”
Section: Data Screening and Extractionmentioning
confidence: 99%
“…In the rGT, performance was slightly impaired after treatment with the 5-HT1A receptor agonist 8-OHDPAT (Zeeb et al 2009). In heroin addicts, treatment with the alpha-2 adrenoceptor agonist clonidine improved decision making performance (Zhang et al 2012). However, the selective NA reuptake inhibitor reboxetine did not influence gambling task performance in healthy subjects (O’Carroll and Papps 2003).…”
Section: Introductionmentioning
confidence: 99%